In vitro shoot proliferation and in vitro and ex vitro root formation of Pyrus elaeagrifolia Pallas - Aygun, Ahmet; Dumanoglu, Hatice (Frontiers in Plant Science, 2015)
Shoot-tip cultures of Pyrus elaeagrifolia Pallas, an important gene source for drought and chlorosis resistance in pear rootstock breeding, were established from a wild mature tree originated from seed. Murashige and Skoog basal medium supplemented with different concentrations of benzyladenine (BA) singly or in combination with auxin was used in the study. In the initial culture, the highest percentages (>80%) of shoot proliferation were obtained in the mediums supplemented with 9.0 μM BA and 0.5 μM indole-3-acetic acid. In the subcultures, the highest shoot proliferation rates were obtained in the medium containing 4.5 and 9.0 μM BA. The shoot proliferation rates ranged from 91.1 ± 2.4 to 96.4 ± 2.0% in the second subculture and from 76.7 ± 7.8 to 89.4 ± 3.3% in the third subculture. In the second subculture, the shoots grown on 9.0 μM BA without auxin produced the best proliferation (10.6 ± 1.6). For the in vitro rooting experiments, the highest rooting rate (54.2 ± 10.4%), root length (10.5 ± 2.4 mm), and root number (2.5 ± 0.6) were obtained from 10 days dark treatment on the medium containing half strength of macronutrients supplemented with 5 μM indole-3-butyric acid (IBA). For the ex vitro rooting experiments, shoot rooting was significantly influenced by 10 mM IBA applied as quick-dip method. The percentage of rooting was 55 ± 9.6% and root number was 1.8 ± 0.3 at this concentration.